Spatial Clustering Group Based OFDMA Access Protocol for the Next Generation WLAN (Xibei Gongye Daxue Xuebao, 2018)
The next generation wireless local area network (WLAN) needs to significantly improve the area throughput in high dense scenario. Orthogonal Frequency Division Multiple Access (OFDMA), considered as the key technology of next generation WLAN, has been adopted by next generation WLAN communication standard. However, the existing studies on the OFDMA protocol have the interference extensions problem, i.e. multiple users are located in the dispersive area, and then the geographical interference area is enlarged. In this paper, a spatial clustering group based OFDMA multiple access protocol (SCG-OFDMA) is proposed. SCG-OFDMA enables the users in close area to form spatial clustering groups dynamically, then the users in the spatial clustering group access channel and transmit data by OFDMA. It reduces the geographical interference area, and enhances the area throughput. The theoretical analysis of SCG-OFDMA is also carried out. The simulation results of SCG-OFDMA are in agreement with the theoretical analysis. Simulation results show that the area throughput of SCG-OFDMA is higher than existing OFDMA protocol and distributing coordination function by 15.98% and 31.26% respectively. It provides a reference to design media access control protocol of the next generation WLAN.